A new angle to mandibular reconstruction: The scapular tip free flap. Issue 7 (30th July 2012) - Yoo, John; Dowthwaite, Samuel A.; Fung, Kevin; Franklin, Jason; Nichols, Anthony
Abstract Background The purpose of this study was to review our experience with the scapular tip free flap for mandibular reconstruction, describe the surgical approach, and highlight specific clinical applications. Methods A retrospective review of all patients undergoing oromandibular reconstruction using a scapular tip free flap at the London Health Sciences Centre was undertaken. Patient demographics, surgical data, and early outcomes were collated. Results Twenty patients were identified. The majority involved mandibular angle and short segment defects (16 of 20). Average length of the segmental defect was 6.2 cm with the longest measuring 8 cm. A single patient required an osteotomy. Six were revision cases. No vein grafts were required. One complete flap failure occurred. Conclusions The natural scapular angle makes the scapular tip flap ideal for mandibular angle reconstruction. Short bone segments can be harvested with little donor‐site morbidity. The long pedicle length may obviate vein grafts. © 2012 Wiley Periodicals, Inc. Head Neck, 2013